Analisis Persepsi Konsumen Terhadap Penggunaan Jasa Gojek - M. Soleh Mauludin; Dewi Ratnawati; Ninik Arianti; Melina Dwi Pryastara; Vivi Adelia Novitawati (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This study aims to find out and analyze consumer perceptions of using Go-Jek services. Using a qualitative approach, consumer behavior theory, and research objects in Kediri, this study resulted in the conclusion that the perception or process that causes a consumer to use Gojek services depends on the stimuli received by the consumer. Every consumer has different motivations and reasons to use Gojek's services. The biggest stimulus that causes the emergence of consumer perception is that Gojek offers attractive promos, where the percentage of those who choose it is 43%.